La varietà delle parlate ladine - Salvi, Giampaolo (Verbum – Analecta Neolatina, 2016)
The article describes the main linguistic features of the Ladin varieties spoken in the Dolomites. After a general introduction and some notes on the external history of these varieties, we give a concise description of Ladin (historical) phonetics and of the nominal and verbal morphology. A more in-depth description is dedicated to syntax in comparison with the neighboring Northern Italian dialects.